The Understanding of the Jamaah Tabligh on Wife Gender Justice: A Maqāṣid Sharīʿa Review - Dri Santoso; Yusefri Yusefri; Laras Shesa; Musda Asmara; Sheikh Adnan Ahmed Usmani; Ahmad Syarifudin (Institut Agama Islam Negeri Batusangkar, 2022)
This research explained the concept of gender justice based on maqāṣid sharīʿa. The concept of gender justice will be used to criticize the teaching of Jamaah Tabligh, which often marginalizes womenfolk in their families. This study is field research that uses the normative approach. The data-collecting techniques of this research are interviews and documentation. The analysis technique of this research is descriptive. The findings of this research were the concept of gender justice of maqāṣid sharīʿa based on that which has the fundamental basis; namely, benefit, and it also cannot be generalized between women another. In Jamaah Tabligh's teaching context, several things should be criticized; negative stigma toward the wife, the wife's livelihood, the children who have been left for months, even years, and the obligation to support the preaching that the husband does. The Jamaah Tabligh's doctrine toward wife is the determining factor for good or bad of human life. This doctrine is not suited to maqāṣid sharīʿa hifdz al-irdl's concept (maintaining honour's concept). Legally the husband is obliged to protect his wife's honor (hifdz al-irdl Jawzah), either physically or psychologically.